The bioenergetic potential of waste arising from the benefit of coffee biomass (Research, Society and Development, 2021)
The research approaches the coffee biomass, which is a source of bioenergy of great economic relevance for the country, the largest producer of processed grains in the world. Coffee straw is a residue from coffee cultivation with high potential due to the possibility of returning most of the nutrients absorbed during fruit formation to the soil. In this perspective, the objective of this study is to understand the bioenergetic potential of residues from the processing of coffee biomass. To observe the property, describe the processing and study the bioenergetic potential of the coffee residue, the methodology used was of an applied nature, qualitative approach and, to reach the objective, exploratory bibliographic research and field research were used. As a result, it can be said that the straw from the coffee biomass processing process is returned to the soil as organic fertilizer, which consequently reduces the costs of chemical fertilization and favors sustainability in rural areas. In the implementation phase of the coffee plantation, the use of straw constitutes a source of nutrients and organic matter. In this context, the study presents the concept and use of this source of bioenergy and important aspects of coffee biomass as its structure and processing stages. However, with the present study it was possible to verify that coffee biomass is an important bioenergetic source.